Blocking circ-CNST suppresses malignant behaviors of osteosarcoma cells and inhibits glycolysis through circ-CNST-miR-578-LDHA/PDK1 ceRNA networks - Rui Hu; Shan Chen; Jianxin Yan (Journal of Orthopaedic Surgery and Research, 2021)
Abstract Background CircRNA CNST (circ-CNST) is a newly identified biomarker for prognosis of osteosarcoma (OS). However, its role in OS progression remains to be well documented. Methods Expression of circ-CNST, microRNA (miR)-578, lactate dehydrogenase A (LDHA), and pyruvate dehydrogenase kinase 1 (PDK1) was detected by quantitative real-time polymerase chain reaction and Western blotting. The physical interaction was confirmed by dual-luciferase reporter assay. Cell behaviors and glycolysis were measured by 3-(4,5-dimethylthiazolyl-2)-2,5-diphenyltetrazolium bromide assay, colony formation assay, flow cytometry, transwell assays, xenograft experiment, and commercial kits. Results Circ-CNST was upregulated in human OS tissues and cells, accompanied with downregulation of miR-578 and upregulation of LDHA and PDK1. There were negative correlations between miR-578 expression and circ-CNST or LDHA/PDK1 in OS tissues. Moreover, high circ-CNST/LDHA/PDK1 or low miR-578 might predict shorter overall survival, advanced TNM stages, and lymph node metastasis. Physically, miR-578 was targeted by circ-CNST, and miR-578 could target LDHA/PDK1. Functionally, blocking circ-CNST and restoring miR-578 enhanced apoptosis rate and suppressed cell proliferation, colony formation, migration, and invasion in 143B and U2OS cells, accompanied with decreased glucose consumption, lactate production, and adenosine triphosphate (ATP)/adenosine diphosphate (ADP) ratio. Furthermore, in vivo growth of U2OS cells was retarded by silencing circ-CNST. Depletion of miR-578 could counteract the suppressive role of circ-CNST deficiency in 143B and U2OS cells, and restoring LDHA or PDK1 partially reversed the role of miR-578 inhibition as well. Conclusion Circ-CNST knockdown could antagonize malignant behaviors and glycolysis of OS cells by regulating miR-578-LDHA/PDK1 axes.